REVIEW OF HEALTH SYSTEM ORGANIZATION APPROACHES TO ESTIMATING SERVICE LEVELS AND EXPENDITURES FOR INPATIENT CARE SERVICES - K. V. Gerasimova; D. V. Fedyaev; M. V. Sura; A. A. Tikhonova; V. V. Omelyanovskiy; M. V. Avksentyeva (Фармакоэкономика)
Objective. To examine approaches to organization and planning as well as expenditures of inpatient care in countries outside of Russia.Methods. A narrative review of published articles and legal documents was conducted. The review focused on health systems organization, planning volumes and costs associated with inpatient care in nine foreign countries (Germany, France, Denmark, Norway, Austria, Great Britain, Canada, Belarus and Kazakhstan) was conducted.Results. In all countries, there is a growth in health care costs both in monetary terms and as a percentage of GDP. The primary policy responses to expenditure growth have focused on outpatient pharmaceuticals, evaluation of medical technologies and reducing volumes of provided hospital care by providing assistance in day hospitals, outpatient or with home-visiting teams. In most countries, responsibility for the organization and planning of inpatient care rests with regional authorities. In all of countries, quality measures are regularly taken as a means to optimize or reduce numbers of beds, reduce hospital length of stay or increase turnover as a means to reduce transaction costs and costs of infrastructure maintenance. The main method of payment for acute care services is based on per case of treatment for a relevant group of diseases (diagnosis related group (DRG)). Planning of medical care in many of these countries is based on financial capacity and performance of previous years. Approaches to planning are typically part of political decision-making, developed at regional or municipal level, leading to variable approaches in health systems characterized by a federation of health regions.